Dietary Inulin Regulated Gut Microbiota and Improved Neonatal Health in a Pregnant Sow Model - Li, Hao; Ma, Longteng; Zhang, Longlin; Liu, Nian; Li, Zhiqing; Zhang, Fan; Liu, Xiang; Ma, Xiaokang (Frontiers in Nutrition, 2021)
The current study aimed to investigate the relationship between maternal dietary fiber intake and piglet health. Multiparous sows were randomly assigned to two groups and fed diets without inulin (control group, n = 20), or 1.6% inulin (1.6IN group, n = 20) respectively. The results indicate that 1.6IN prevented the prolonged farrowing duration of sows (P <0.05) and shortened the average piglet birth interval (P <0.10). Additionally, 1.6IN decreased the piglet percentage of born weak and the piglet percentage of hyperthermia after birth (P <0.01). Compared to the control group, the 1.6IN group had lower concentration of urea nitrogen in the colostrum, and also prevented diarrhea, increased litter gain, survival rate and average daily gain for suckling piglets (P < 0.05). Moreover, 1.6IN decreased the relative abundance of Firmicutes, Cyanobacteria, and Streptococcus, and increased the relative abundance of Bacteroidetes, Desulfovibrio, Paludibacter, CF231, and Prevotella. Overall, the current study showed that maternal fiber nutrition during pregnancy regulated the health of offspring, and the response of the maternal intestinal microbes played an important role in intervening the phenotype of sows and neonatal piglets.